(untitled) - Richards, Jack C. (Oxford, 2004)
It's the book of comprehensive listening skills course
Nghe - Nói C1.1
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Textbooks for foreign speakers,luyện nghe,listening,Tài liệu dành cho người nước ngoài